Finance-growth nexus : evidence from Angola - Ferreira, Manuel Ennes (2022)
This study examines the relationship between financial development and economic growth in Angola for the period of Q12002 to Q42018. The results show that there is evidence of a long-run relationship between financial development and real GDP per capita, when using the Bound test approach for cointegration. Furthermore, the results of the Error Correction Model (ECM) indicate that financial development has a negative impact on GDP growth when considering credit to private and broad money as proxies for financial development. On the other hand, the degree of intermediation has a positive impact on GDP growth. The Toda–Yamamoto causality test was carried out, which indicates a unidirectional causality relationship, running from real GDP per capita to a purely financial development proxy, which shows demand-following responses. Consequently, policymakers should adopt policies that sustain the benefits of financial developments for economic growth.